(untitled) (قضايا سياسية, 2022)
Recently, empowerment subject has received local and global attention as it is a deliberate process, whose goal and means is the human being, in order to achieve integrated social and economic growth. Further, it aimed at developing and refining individual skills and enhancing his self-esteem. In addition, to increasing his ability to take decisions and transforming them into effective procedures to make the decision. Accordingly, this research paper presents a theoretical study on the reality of Iraqi women in social care field, where they suffer from a lack of financial specializations in addition to the arbitrariness of the conditions for inclusion in the care salary. The paper also deals with the reality of women in higher education, where they suffer from almost absolute deprivation from taking over university leadership, as well as marginalization and weak practice in terms of academic freedom, which considered as a type of violence. The study concluded with a number of proposals for the promotion and women empowerment in the two mentioned fields, starting with encouraging small projects to approving the quota principle as a starting point to empowering women in higher education.